Efficient laser production of energetic neutral beams. (15th February 2016) - Mollica, F; Antonelli, L; Flacco, A; Braenzel, J; Vauzour, B; Folpini, G; Birindelli, G; Schnuerer, M; Batani, D; Malka, V
Abstract: Laser-driven ion acceleration by intense, ultra-short, laser pulse has received increasing attention in recent years, and the availability of much compact and versatile ions sources motivates the study of laser-driven sources of energetic neutral atoms. We demonstrate the production of a neutral and directional beam of hydrogen and carbon atoms up to 200 keV per nucleon, with a peak flow of atom s −1 . Laser accelerated ions are neutralized in a pulsed, supersonic argon jet with tunable density between cm −3 and cm −3 . The neutralization efficiency has been measured by a time-of-flight detector for different argon densities. An optimum is found, for which complete neutralization occurs. The neutralization rate can be explained only at high areal densities (> cm −2 ) by single electron charge transfer processes. These results suggest a new perspective for the study of neutral production by laser and open discussion of neutralization at a lower density.